Bone : Out from Boneville - Smith, Jeff, 1960- (Bone, 2005)
Fone Bone, Phoney Bone, and Smiley Bone are run out of their home, Boneville, and become separated in the wilds, but better fortune begins when the three cousins reunite at a farmstead in a deep forested valley, where Fone meets a young girl named Thorn.